2017
DOI: 10.3390/brainsci7030025
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Stress and Injury Caused by HIV-1, cART and Drug Abuse: Converging Contributions to HAND

Abstract: Multiple mechanisms appear to contribute to neuronal stress and injury underlying HIV-associated neurocognitive disorders (HAND), which occur despite the successful introduction of combination antiretroviral therapy (cART). Evidence is accumulating that components of cART can itself be neurotoxic upon long-term exposure. In addition, abuse of psychostimulants, such as methamphetamine (METH), seems to compromise antiretroviral therapy and aggravate HAND. However, the combined effect of virus and recreational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 242 publications
(380 reference statements)
1
32
0
Order By: Relevance
“…Malignancies, depression, and immune dysfunctions are specifically linked to cognitive and behavioral abnormalities as are antiretroviral drugs (ARVs) themselves. The latter plays a role in direct neurotoxicity and consequent neuropsychiatric compromise [ 6 , 7 ]. Among them, to date, efavirenz is known to affect neuronal function [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malignancies, depression, and immune dysfunctions are specifically linked to cognitive and behavioral abnormalities as are antiretroviral drugs (ARVs) themselves. The latter plays a role in direct neurotoxicity and consequent neuropsychiatric compromise [ 6 , 7 ]. Among them, to date, efavirenz is known to affect neuronal function [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In HIV studies, degree of neurocognitive impairment has been shown to correlate with reduced NAA levels [ 32 ]. Although neuronal apoptosis has been observed in brains of individuals with HAND [ 62 , 63 ], the general consensus is that prolonged neuronal dysfunction precipitates permanent neuronal loss. Reversible alterations in synaptodendritic networks have been demonstrated in the setting of HIV infection [ 16 , 64 ], and damage to these structures is a strong pathological correlate of neurocognitive impairment due to HIV [ 33 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug abuse and addiction can cause a greater neurocognitive impairment and poorer HAART adherence compared to non-drug users [3,27,38]. Indeed, HAART slows down the progression of HIV to AIDS, and so incomplete adherence can lead to immunosuppression and drug resistant HIV [34], while non-adherence increases HIV-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of recreational drugs have been found to induce CNS impairment independent of the effects of HIV infection [3]. Consequently, people living with HIV/AIDS face an additional burden of psychiatric comorbidity, where approximately 40% of patients with HIV infection will develop CNS involvement [4].…”
Section: Introductionmentioning
confidence: 99%